Răspuns :
a+b+c=7,2
a = 2b-1,5
a = c+1,8 c= a-1,8 = 2b-1,5-1,8=2b-3,3
2b-1,5+b+2b-3,3=7,2
5b=7,2+1,5+3,3
5b=12
b=12:5=2,4
b=2,4 a= 2b-1,5=2*2,4-1,5=3,3
c= 2b-3,3=2*2,4-3,3=1,5
a+b+c=3,3+2,4+1,5=7,2
a = 2b-1,5
a = c+1,8 c= a-1,8 = 2b-1,5-1,8=2b-3,3
2b-1,5+b+2b-3,3=7,2
5b=7,2+1,5+3,3
5b=12
b=12:5=2,4
b=2,4 a= 2b-1,5=2*2,4-1,5=3,3
c= 2b-3,3=2*2,4-3,3=1,5
a+b+c=3,3+2,4+1,5=7,2
a+b+c=7,2
a=2b+1,5
a+1,8=c
inlocuim
2b+1,5+a+1,8=7,2
2b+a=7,2+1,5+1,8
Inlocuim iar
2b+2b+1,5=10,5
4b=10,5+1,5
4b=12
impartim la 4 ..4b=12/4
b=3
a=2•3+1,5
a=6+1,5
a=7,5
a=2b+1,5
a+1,8=c
inlocuim
2b+1,5+a+1,8=7,2
2b+a=7,2+1,5+1,8
Inlocuim iar
2b+2b+1,5=10,5
4b=10,5+1,5
4b=12
impartim la 4 ..4b=12/4
b=3
a=2•3+1,5
a=6+1,5
a=7,5